Financial Management Relevance: Good Corporate PAUD/TK ABA Aisyiyah Kartasura - Nashirotun Nisa Nurharjanti; Rina Trisnawati (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Community service was carried out to provide explanations related to financial management in order to achieve Good Corporate within PAUD/TK Aba Kartasura. The activity began by explaining the importance of financial records at the treasurer of PAUD/TK ABA in Kartasura. This is done because based on the initial survey the records that have been carried out by the treasurer are still varied. This means that there are treasurers who have recorded in accordance with their activities, but there are records that are combined in nature so that they will experience difficulties when carrying out the tracing process. In addition, it is related to the writing of receipts that have not been carried out so that administratively it is not complete if it is adjusted to the occurrence. Thus, the initial step taken is to provide an explanation through socialization beforehand so that there is an understanding and common perception among all treasurers of PAUD/TK ABA in Kartasura. The socialization took the form of delivering material followed by a question and answer session. The results of the question and answer obtained various forms of recording so it is necessary to do homogeneity of recording. It is hoped that financial management will be informative so that Good Corporate can be realized in PAUD/TK ABA Kartasura.